THE INFLUENCE OF LIQUIDITY, INTEREST RATE, AND COMPANY VALUE ON PT GUDANG GARAM TBK'S STOCK PRICE, 2011-2019 - eko budianto (Universitas Islam Lamongan, 2022)
The research objectives can be presented as follows: To analyze whether liquidity, Interest rates and goodwill has an effect on stock prices at PT Gudang Garam Tbk, to analyze which of liquidity, interest rates, and goodwill has the most dominant influence on PT. Gudang Garam Tbk. This study is a quantitative descriptive study, namely to determine the effect of liquidity, interest rates, and firm value on stock prices. The results of hypothesis testing are obtained that simultaneously the independent variables are Liquidity (Current Ratio), Interest Rate (BI Rate), and Firm Value ( Price Earning Ratio) has abig impact on stock price of PT Gudang Garam Tbk. Liquidity (Current Ratio) (X1) does not have a significant and negative impact on the share price, this can be proved by a considerable value of 0.133 while the ttable value of 2.02809. Interest rates (BI rate) have a significant and negative effect on stock prices, this can be proven by the tcount value of -4.174 while the ttable value of 2.02809. The value of the company (Price Earning Ratio) (X3) has no significant and positive effect on stock prices, this can be proven by the t-value for the X3 variable. Firm value (Price Earning Ratio) is 0.147 while the ttable value is 2.02809.